Taxonomic reassessment of the Herpetoreas xenura (Wall, 1907) (Squamata: Serpentes: Natricidae) from Myanmar with description of a new species - Nguyen, Tan Van; Lalremsanga, Hmar Tlawmte; Biakzuala, Lal; Vogel, Gernot (European Journal of Taxonomy, 2024)
The review of the taxonomic status of Herpetoreas xenura species complex, based on morphological and molecular data, revealed a new species from Myanmar, which we describe as Herpetoreas davidi sp. nov. from the Rakhine Yoma Elephant Wildlife Sanctuary in Rakhine State. It is suggested to be a sister species to Herpetoreas pealii and Herpetoreas xenura sensu stricto, and can be separated from the latter species by a combination of morphological and scalation characters, and by its pattern. Another population from the Htamanthi Wildlife Sanctuary, Sagaing Region, was previously confused with H. xenura. However, as a closer examination of its morphology, shows it to be closer to Hebius khasiensis, we herein tentatively refer to this population as Hebius khasiensis, pending further molecular data confirming its taxonomic status. Consequently, we propose to temporarily remove Herpetoreas xenura from the fauna of Myanmar. Further studies, especially in the northwestern region of Myanmar, such as near border with India in Chin Hills and Naga Hills, are required. An updated key for the species of Herpetoreas is also provided.